Effects of Increasing Standardized Ileal Digestible Valine:Lysine Ratio on Growth Performance of Finishing Pigs - Samantha A. Swanson; Andy W. Boschert; Mikayla S. Spinler; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
Two experiments were conducted to evaluate the effects of increasing standardized ileal digestible (SID) Val:Lys ratio on the growth performance of 85 to 150 lb (Exp. 1) and 195 to 260 lb (Exp. 2) finishing pigs. In Exp. 1,647 pigs (DNA 600 × 241) were randomly allotted to one of six dietary treatments with eight or nine pigs per pen and 12 replications per treatment. Diets were corn-soybean meal-based, and low and high Val diets were manufactured and blended to create intermediate Val:Lys ratio diets. Diets were formulated to contain 0.90% SID Lys, and treatments consisted of SID Val:Lys ratios of 60, 63, 66, 69, 72, and 75%. At the conclusion of the 27-d study, all pigs were fed a common diet for 30 days and then randomly re-allotted to one of six diets formulated to contain 0.65% SID Lys and SID Val:Lys ratios of 63, 66, 69, 72, 75, and 78% (Exp. 2). In both experiments, blood samples were drawn from three pigs per pen on d 15 for plasma urea nitrogen (PUN) analysis. In Exp. 1, final BW, ADG, and ADFI increased (quadratic, P < 0.05) as Val:Lys ratio increased. Pigs fed the diet with 66% SID Val:Lys ratio had the greatest ADG, whereas pigs fed 72% SID Val:Lys ratio had the greatest ADFI. As the Val:Lys ratio increased, feed efficiency worsened (linear, P < 0.05). Valine and Lys intake increased (quadratic, P < 0.05) as the Val:Lys ratio increased with the greatest Val intake observed at the 72% SID Val:Lys ratio. Valine and Lys intake per kg of gain increased (linear, P < 0.05) as the level of Val in the diet increased. Plasma urea nitrogen decreased (linear, P < 0.05) as the Val:Lys ratio increased. In Exp. 2, ADG and ADFI increased (linear, P < 0.05) as Val:Lys increased. However, for ADG there was little improvement from feeding greater than 69% SID Val:Lys. There were no effects (P > 0.05) of SID Val:Lys on final BW, feed efficiency, or PUN. Valine intake, Lys intake, and Val intake per kg of gain increased (linear, P < 0.05) as the Val:Lys ratio increased. There were no differences (P > 0.05) observed in Lys intake per kg of gain. Results of this study suggest the SID Val:Lys requirement for finishing pigs is approximately 66% for 85 to 150 lb and 69% for 195 to 260 lb.
Keywords: amino acid; finishing pig; valine